Alcohol consumption and associated risk factors in Burkina Faso: results of a population-based cross-sectional survey. Issue 2 (10th February 2022) - Bonnechère, Bruno; Samadoulougou, Sékou; Cisse, Kadari; Tassembedo, Souleymane; Kouanda, Seni; Kirakoya-Samadoulougou, Fati
Abstract : Objectives: Lifestyle modifiable risk factors are a leading preventable cause of non-communicable diseases, with alcohol consumption among the most important. Studies characterising the prevalence of alcohol consumption in low-income countries are lacking. This study describes the prevalence of different levels of alcohol consumption in Burkina Faso and its associated factors. Design: Data from the 2013 Burkina Faso WHO STEPwise Approach to Surveillance survey were analysed. The prevalence of alcohol consumption over the last 30 days was recoded into categories according to WHO recommendations: low, mid or abusive alcohol consumption. Multinomial logistic regression analyses identified factors associated with the different levels of alcohol consumption. Setting: Population-based cross-sectional survey in Burkina Faso. Participants: 4692 participants of both sexes aged 25–64 years were included in the study. Results: In the whole sample, 3559 participants (75.8% (72.5%–78.7%)) were not consuming any alcohol, 614 (12.9% (10.9%–15.3%)) had low alcohol consumption, 399 (8.5% (7.1%–10.1%)) had mid alcohol consumption and 120 (2.7% (2.0%–3.7%)) had abusive consumption. Age was associated with alcohol intake with a gradient effect and older people having a higher level of consumption (adjusted OR (AOR): 2.36, 95% CI (1.59 to 3.51) for low consumption, 2.50 (1.54 to 4.07) for mid consumption and 2.37 (1.01 to 5.92) for abusive consumption in comparison with no consumption). Tobacco consumption was also significantly associated with alcohol intake with a gradient effect, those with higher tobacco consumption being at higher risk of abusive alcohol intake (AOR: 6.08 (2.75 to 13.4) for moderate consumption and 6.58 (1.96 to 22.11) for abusive consumption). Conclusion: Our data showed an important burden of alcohol consumption in Burkina Faso, which varied with age and tobacco use. To effectively reduce alcohol consumption in Burkina Faso, comprehensive control and prevention campaigns should consider these associated factors.